Role Of Eps As An Intervening Variable Between Profitability And Solvency Ratio On Stock Price - Ajeng Puspitasari; Enny Susilowati Mardjono (Jurnal Telekomunikasi dan Informatika, 2024)
The research was conducted with the aim of determining the role of Gross Profit Margin (GPM), Debt to Equity Ratio (DER), Return On Assets (ROA) in influencing Stock Prices with Earning Per Share (EPS) as an intervening variable. The population of this research uses the Property, Real Estate and Building Construction Sectors listed on the IDX for the 2021-2023 period. The sampling method uses purposive sampling, so that from a population of 166 companies, 107 companies were obtained that met the criteria. This research analysis tool is assisted by IBM SPSS version 20. The analysis technique used in this research is path analysis. The results of the study stated that ROA and EPS had a partial impact on stock prices, while other variables such as GPM and DER didn’t affect stock prices. DER and ROA contributed to EPS, while GPM didn’t contribute to EPS. The results of the Path Analysis stated that GPM didn’t have a significant effect on Stock Prices through EPS as an intervening. DER didn’t have a significant effect on Stock Prices through EPS as an intervening. ROA didn’t have a significant effect on Stock Prices through EPS as an intervening.